Teaching Interpreting by Distance Mode: An Empirical Study - Ko, Leong (Meta, 2008)
AbstractThis paper is based on an empirical study of teaching liaison interpreting – specifically, dialogue interpreting, consecutive interpreting and sight translation – by distance mode. In this research, two groups of students were recruited – the experimental group to be taught by distance mode and a control group trained face-to-face. The training program lasted for 13 weeks or 39 hours, with three contact hours per week. The training followed the principle that no face-to-face contact with distance students was made during the training process, including the final examination. The major media used in the research included sound-only teleconferencing, telephone and the Internet. Students’ interpreting skills including language transfer and paralinguistic skills were assessed in different tests including an independent national test. The results of the research indicate that students trained by distance mode can achieve a level similar or comparable to those trained in the face-to-face manner in terms of interpreting ability and skills. The research has generated pedagogical implications for future attempts to teach interpreting by distance mode.